1998
DOI: 10.1007/s000240050167
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a Rock Failure Criterion Based on Circumferential Tensile Strain

Abstract: Uniaxial compression, triaxial compression and Brazialian tests were conducted on several kinds of rock, with particular attention directed to the principal tensile strain. In this paper we aim to clarify the effects of the experimental environment -such as confining pressure, loading rate, water content and anisotropy-on the critical tensile strain, i.e., the measured principal tensile strain at peak load.It was determined that the chain-type extensometer is a most suitable method for measuring the critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Attributed to the bonding effect of ice crystals, the UCS was higher for rock samples with a higher ice content, and the UCS increase was not significant under −4 °C because of the constant frozen water content. With the temperature decrease, the UCS of the rocks increased and the critical compressive strain decreased [38]. In Figure 3, we can see that the specimens became brittle with the decrease of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Attributed to the bonding effect of ice crystals, the UCS was higher for rock samples with a higher ice content, and the UCS increase was not significant under −4 °C because of the constant frozen water content. With the temperature decrease, the UCS of the rocks increased and the critical compressive strain decreased [38]. In Figure 3, we can see that the specimens became brittle with the decrease of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Not on permeability but it was also clarified that the critical extensile strain (extensile strain at peak load point [Fujii et al, 1998]) of Kimachi sandstone and Inada granite was much less sensitive to temperature than critical compression strain (compressive strain at peak load point).…”
Section: Discussionmentioning
confidence: 99%
“…No significant influences were observed in the tangent modulus and the residual strength. No significant effects of temperature on the critical extensile strain (CES, circumferential or lateral extensile strain value at peak load point) [Fujii et al, 1998]) were observed. However, the critical compressive strain (CCS, axial strain value at peak load point) at 353 K was larger than that at 295 K (Fig.…”
Section: The Effects Of Deformation and Failure On Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Stacy also suggests the value of permissible tensile strain: ε l = 0.0073% for a certain congloment reef and ε l = 0.0175% for a diabase. Further researches are continued by Sakurai et al 19, 20, Fujii et al 21, Li et al 22, concerning the improvement of the criterion and the evaluation of the corresponding parameter ε l , which is reported to range between ε l = 0.1–1% according to the different laboratory test resources 17.…”
Section: Relaxation Mechanism and Criterionmentioning
confidence: 99%